Report on the geology and physical character of the Nastapoka Islands, Hudson Bay [electronic resource] - Low, A. P. (Albert Peter), 1861-1942.; Geological Survey of Canada. (Ottawa : S.E. Dawson, 1903)
At head of title: . Geological Survey of Canada . Also available in French. See CIHM microfiche no. 97730. "Part DD, Annual report, vol. xiii, 1900." "No. 819." Electronic reproduction. Mode of access: Internet. 44